Effects of the COVID‐19 Pandemic on Patients Living With Vasculitis. Issue 1 (8th December 2020) - Banerjee, Shubhasree; George, Michael; Young, Kalen; Venkatachalam, Shilpa; Gordon, Jennifer; Burroughs, Cristina; Curtis, David; Ferrada, Marcela; Gavigan, Kelly; Grayson, Peter C.; Kullman, Joyce; Danila, Maria I.; et al.
Abstract : Objective: This study aimed to analyze the concerns and health‐related behaviors in patients with vasculitis during the early phase of the coronavirus disease 2019 (COVID‐19) pandemic in North America. Methods: Patients with vasculitis in North America were invited to complete an online survey through the Vasculitis Patient‐Powered Research Network in collaboration with the Vasculitis Foundation and the Relapsing Polychondritis Foundation. Questions focused on concerns and behaviors related to doctors' visits, tests, medication, and telehealth use. Factors affecting their concern and health‐related behaviors were determined. Results: Data from 662 patients were included: 90% of patients were White, 78% were women, 83% expressed moderate or high levels of concern about COVID‐19, and 87% reported that their vasculitis moderately or extremely affected their level of concern. Older age, female sex, lung disease, and immunosuppression were associated with greater concern. Doctors' visits, laboratory tests, and other tests were avoided by 66%, 46%, and 40% of patients, respectively. Younger age, urban location, higher income, higher concern levels, and prednisone use (>10 mg/day) were associated with greater likelihood of avoiding visits or tests. Ten percent of patients on immunosuppressive therapy stopped their medication. Twenty‐nine percent patients on rituximab avoided an infusion. Forty‐four percent of patients had telehealth visits; more visits were reported for younger patients, for patients on glucocorticoids, and in Canada versus the United States. Conclusion: During the COVID‐19 pandemic, patients with vasculitis have high levels of concern and exhibit potentially harmful health‐related behaviors. Health care use varies across different demographic groups and geographic regions. Specific strategies are warranted to facilitate engagement of these patients with the health care system during the pandemic.